Penguatan Pemahaman Berinternet Yang Aman Bagi Orang Tua di Desa Tuntungan I Kec. Pancur Batu - Amir, Saiful; Nurliana; Faizin Ridho; Rizki Ananda; Ferdi Riza; Mardiah (Unity Academy, 2022)
Growth in the number of internet users in Indonesia without being balanced with knowledge and understanding of the negative impacts it can cause problems among the community. For example, fake news (hoax), SARA issues and radicalism on the internet become a threat to society, especially the younger generation in the future. The role of parents is very necessary to accompany their children to avoid the negative impact of internet users. However, the challenge faced is the lack of understanding of parents about the negative impact of internet users, especially for children. The objectives of Community Service activities in Tuntungan Village I Kec. Pancur Batu Deli Serdang are: a) increasing public understanding, especially parents, of the impact of internet use on children, b) strengthening digital images as learning media, c) providing adequate information to parents in responding to the negative impact of internet use on children. The implementation method is carried out through training activities and focus group discussions (FGD) to the village community of Tuntungan I Kec. Pancur Batu Kab. Deli Serdang. The result of community service activities is an increased understanding of negative impacts. This is shown through the results of the questionnaire after socialization and training, namely 86% responded strongly agree. Given the increasing number of applications or software and the flow of information on the internet, it is necessary to have continuous socialization and training efforts to improve skills and knowledge, so as to minimize the negative impact caused by arise from the use of the internet.